Productive Maintenance in Polygamous Families: Qur’anic Perspectives and Socio-Economic Practices in Aceh Rayeuk - Iskandar Usman, Mizaj (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
This study utilizes a qualitative framework, integrating empirical research and interpretive thematic analysis to examine productive maintenance within polygamous marriages in Aceh Rayeuk. Grounded in Qur’anic principles of financial maintenance, the analysis evaluates data gathered through field observations of household economic practices and in-depth interviews with polygamous couples, village officials, and community leaders. The findings indicate that financial maintenance within these households extends beyond merely fulfilling consumptive needs; it is actively directed toward productive endeavours, including business capital, agricultural land management, property investment, fisheries assets, and children’s education. Interpretive thematic analysis demonstrates that these practices serve as strategies for long-term economic sustainability and function as tangible manifestations of the principle of justice (‘adl) in polygamous marriages. From an Islamic legal perspective, these practices align with the Qur’anic concept of bil-ma‘rūf, which mandates providing financial maintenance in a proper, proportional, and contextually appropriate manner that reflects prevailing socio-economic realities. Furthermore, this study highlights that the efficacy of productive maintenance is contingent upon proactive financial management, the active participation of wives, and local economic conditions. Ultimately, these factors serve as crucial indicators for maintaining the economic stability and overall welfare of polygamous families within the Aceh Rayeuk community.